Legal aspects of inclusion of greenhouse gas emissions and removals resulting from activities related to land use, land use change and forestry - Leśkiewicz, Katarzyna (Przegląd Prawa Rolnego, 2019)
The aim of the article is to assess whether the binding legal regulations, including the national ones, may be assessed as conducive to the achievement of the objectives of the EU’s Energy Union in the scope of forest land management. In particular, whether the solutions adopted by Poland with regard to forest management may be considered as supporting the achievement of the objectives of the LULUCF regulation. The mechanisms of accounting for CO2 emissions and removals are based on historical data in the initial assumptions, and are intended to serve the implementation of the effects projected for the future. It is impossible to determine a priori whether the regulation in question will bring specific economic benefits or losses in terms of timber harvesting in state-owned forests. After all, it will depend on the result of accounting for emissions and removals from LULUCF.